2022
DOI: 10.1590/1678-9865202235e210079
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of taxifolin on acrylamide-induced heart damage in rats

Abstract: Objective Acrylamide is a toxic compound widely used in industrial sectors. Acrylamide causes reactive oxygen species formation and the subsequent lipid peroxidation reaction, which plays an important role in the pathogenesis of oxidative damage. Taxifolin is a flavonoid with antioxidant properties that inhibit reactive oxygen species formation. In this study, we aimed to investigate the preventive effect of taxifolin on acrylamide-induced oxidative heart damage. Methods The rats were divided into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In accordance with our results, several investigations have shown that the cardioprotective action of TAX is associated with reduced oxidative markers and elevated antioxidant components, resulting in ameliorated oxidative injury to the myocardium [ 39 , 40 , 49 ]. Furthermore, TAX exhibited tissue protective effect against chemically-induced oxidative damage in various experimental models, such as acrylamide-induced heart [ 21 ] and kidney injury [ 50 ], alcohol [ 25 ] and carbon tetrachloride (CCl 4 )-induced liver injury [ 25 ], and methanol-induced oxidative optic nerve damage [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with our results, several investigations have shown that the cardioprotective action of TAX is associated with reduced oxidative markers and elevated antioxidant components, resulting in ameliorated oxidative injury to the myocardium [ 39 , 40 , 49 ]. Furthermore, TAX exhibited tissue protective effect against chemically-induced oxidative damage in various experimental models, such as acrylamide-induced heart [ 21 ] and kidney injury [ 50 ], alcohol [ 25 ] and carbon tetrachloride (CCl 4 )-induced liver injury [ 25 ], and methanol-induced oxidative optic nerve damage [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…(+)-Taxifolin (TAX; C 15 H 12 O 7 , Figure 1 ) is a natural flavonoid present mainly in olive oil, grapes, and onions, and one which possesses several pharmacological actions, including radical scavenging and anti-inflammatory properties [ 19 , 20 ]. Indeed, TAX was shown to prevent against acrylamide-induced heart damage in rats by decreasing oxidative stress and enhancing antioxidants [ 21 ]. Furthermore, TAX protected against renal damage induced by unilateral ureteral obstruction (UUO) in rats via suppressing oxidative tissue injury, inflammation, and fibrosis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%